Influence of acid systems on bottomhole zone decolmatization and set cement stability - Stavychnyi, Ye.M.; Rudyi, S.M.; Femiak, Ya.M.; Tershak, B.A.; Piatkivskyi, S.A.; Klymyuk, M.M.; Kindrat, V.V. (Physics and Chemistry of Solid State, 2024)
The state of the bottomhole zone during drilling was assessed on the example of well No. 47 Stynava. Based on the study of the impact of drilling fluid on the filtration and capacitance characteristics of the core material, it was found that the colmatation screen on the core material can be eliminated by acid treatment. The studies and results of operations at wells of PJSC “Ukrnafta” have confirmed the effectiveness of oil recovery enhancement methods, among which the acid treatment of formations, whichare used both for cleaning of well bottomhole zone and forintensification. The main technological parameters of a few cementing materials and mixtures, as well as the physical-and-mechanical properties of set cement based on them, were studied. The effect of acid treatment used during intensification on set cement was evaluated. It has been established that base cements and mixtures based on them are subjected to a significant aggressive effect of acids, which provokes the destruction of set cement. The results of the study substantiate the expediency of using composite plugging cements for well cementing in difficult conditions where the set cement of the insulating ring can be exposed to acid exposure.